Shiga toxin 2 from enterohemorrhagic Escherichia coli induces reactive glial cells and neurovascular disarrangements including edema and lipid peroxidation in the murine brain hippocampus - Berdasco, Clara Valentina (2019)
Background: Shiga toxin 2 from enterohemorrhagic Escherichia coli is the etiologic agent of bloody diarrhea, hemolytic uremic syndrome and derived encephalopathies that may result to death in patients. Being a Gram negative bacterium, lipopolysaccharide is also released. Particularly, the hippocampus has been found affected in patients intoxicated with Shiga toxin 2. In the current work, the deleterious effects of Shiga toxin 2 and lipopolysaccharide are investigated in detail in hippocampal cells for the first time in a translational murine model, providing conclusive evidences on how these toxins may damage in the observed clinic cases. Methods: Male NIH mice (25 g) were injected intravenously with saline solution, lipopolysaccharide, Shiga toxin 2 or a combination of Shiga toxin 2 with lipopolysaccharide. Brain water content assay was made to determine brain edema. Another set of animals were intracardially perfused with a fixative solution and their brains were subjected to immunofluorescence with lectins to determine the microvasculature profile, and anti-GFAP, anti-NeuN, anti-MBP and anti-Iba1 to study reactive astrocytes, neuronal damage, myelin dysarrangements and microglial state respectively. Finally, the Thiobarbituric Acid Reactive Substances Assay was made to determine lipid peroxidation. In all assays, statistical significance was performed using the One-way analysis of variance followed by Bonferroni post hoc test. Results: Systemic sublethal administration of Shiga toxin 2 increased the expressions of astrocytic GFAP and microglial Iba1, and decreased the expressions of endothelial glycocalyx, NeuN neurons from CA1 pyramidal layer and oligodendrocytic MBP myelin sheath from the fimbria of the hippocampus. In addition, increased interstitial fluids and Thiobarbituric Acid Reactive Substances-derived lipid peroxidation were also found. The observed outcomes were enhanced when sublethal administration of Shiga toxin 2 was co-administered together with lipopolysaccharide. Conclusion: Systemic sublethal administration of Shiga toxin 2 produced a deterioration of the cells that integrate the vascular unit displaying astrocytic and microglial reactive profiles, while edema and lipid peroxidation were also observed. The contribution of lipopolysaccharide to pathogenicity caused by Shiga toxin 2 resulted to enhance the observed hippocampal damage.